2016
DOI: 10.1002/cphc.201600767
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Explosive Vapors: The Roles of Exciton and Molecular Diffusion in Real‐Time Sensing

Abstract: Time-resolved quartz crystal microbalance with in situ fluorescence measurements are used to monitor the sorption of the nitroaromatic (explosive) vapor, 2,4-dinitrotoluene (DNT) into a porous pentiptycene-containing poly(phenyleneethynylene) sensing film. Correlation of the nitroaromatic mass uptake with fluorescence quenching shows that the analyte diffusion follows the Case-II transport model, a film-swelling-limited process, in which a sharp diffusional front propagates at a constant velocity through the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Alongside this, diffusion of the nerve agent analyte in the sensing films is another critical factor influencing the detection performance. Studies on the fluorescence quenching–based detection of nitro‐containing explosive vapors using organic fluorophores have shown that analyte diffusion is a first order parameter . The diffusion of nerve agents or simulants into sensing films has not been reported.…”
Section: Analyte Diffusion In Solid‐state Sensing Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alongside this, diffusion of the nerve agent analyte in the sensing films is another critical factor influencing the detection performance. Studies on the fluorescence quenching–based detection of nitro‐containing explosive vapors using organic fluorophores have shown that analyte diffusion is a first order parameter . The diffusion of nerve agents or simulants into sensing films has not been reported.…”
Section: Analyte Diffusion In Solid‐state Sensing Filmsmentioning
confidence: 99%
“…However, whether the success of the approach is due to favorable analyte diffusion and/or fast reaction between the sensing material and the analyte is as yet unclear. To clarify this question, further investigation on the analyte diffusion using specific measurements is necessary, e.g., by quartz crystal microbalance measurements …”
Section: Analyte Diffusion In Solid‐state Sensing Filmsmentioning
confidence: 99%
“…A large panel of analytical techniques going from expensive and sophisticated instrumentations to low-cost portable detectors is currently available for this purpose. Of particular interest, fluorescent vapor-phase sensors have been extensively developed [1][2][3][4][5][6] in concomitance with the emergence of a huge variety of fluorescent sensing materials such as conjugated organic/inorganic polymers 2,7 , dendrimers [8][9][10] , molecular imprinted polymers 11 , supramolecular 3D-architectures 12 . Small fluorescent molecules 1 are also attractive since they constitute relevant building block motifs for self-assembly thin-film sensors.…”
mentioning
confidence: 99%
“…Recent studies have indicated that long range exciton diffusion is not occurring in these materials and that the magnitude of the fluorescence quenching response is primarily determined by the analyte diffusion process. 19 PPVs are also prone to aggregation-induced quenching in the solid state, 6 hence similar methods have been employed to prevent losses to the PLQY. Shown in Figure 1.8 are three PPVs, two of which incorporate bulky phenyl substituents to prevent self-quenching by π-stacking interactions.…”
Section: Linear Conjugated Polymersmentioning
confidence: 99%
“…In particular, it was shown that the high sensitivity of so-called amplifying fluorescent polymers is not due to long range exciton diffusion, but the relatively high analyte concentration in the diffusion front that moves through the sensing film as the analyte is sorbed. 19 To quantify the amount of analyte the poly(dendrimer) films can accommodate and the distribution of the analyte within the film, neutron reflectometry was performed. This technique has been successful in showing that:…”
Section: Quantifying Analyte Vapour Uptake and Distribution In Thin Fmentioning
confidence: 99%